Charge asymmetric dissociation of a CO+ molecular-ion beam induced by strong laser fields - Kling, Nora G.; McKenna, J.; Sayler, A. M.; Gaire, B.; Zohrabi, M.; Ablikim, U.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2013)
Charge asymmetric dissociation into C2++O following ionization of a CO+ molecular-ion beam with intense ultrashort (7–40-fs) laser pulses is studied using a coincidence three-dimensional momentum imaging method. The data suggest that allowing the molecule enough time to stretch within a laser pulse such that it ionizes beyond the curve crossings of the C2++O and C++O+ potentials enhances the otherwise hard-to-reach charge asymmetric dissociation channel.